IMPROVING STUDENTS’ VOCABULARY ACHIEVEMENT THROUGH MAGNETIC BOARD MEDIA - Firdayanti Firdaus (Journal MELT (Medium for English Language Teaching), 2018)
The purpose of this study was to find out how the application of the Magnetic Board Media to improve students’ English vocabulary achievement. This is a Classroom Action Research which used the Kemmis & Mc. Taggart Model in two cycles. Each cycle consists of four stages: plans, actions, observations, and reflections. The subjects in this study were students of Grade IV-A of The State Elementary School No. 104202 Bandar Setia Percut Sei Tuan. The object of this study was the application of Magnetic Board Media to improve the students’ vocabulary achievement. Based on the results of the study, it was found that the percentage of completeness from pre-action, Cycle-I and Cycle-II increased. The percentage of student’s completeness in pre-action was 18%, in the Cycle-I was 53%, and in the Cycle-II was 87%. There was a significant increase 69% from pre-action to cycle-II. Thus, this study was successful and can be said that the use of the magnetic board media can improve students' vocabulary achievement, long term memory, and motivation.